2021
DOI: 10.1519/jsc.0000000000003272
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activation Patterns During Variable Resistance Deadlift Training With and Without Elastic Bands

Abstract: The purpose of this study was to determine the effects of band-assisted variable resistance training on muscular activity in the lower limbs and barbell kinematics during the concentric phase of the deadlift. Fifteen resistance trained men (mean ± SD: 28.7 ± 9.3 y; 1.80 ± 0.90 m; 92.5 ± 15.1 kg) performed six deadlift repetitions during four loading conditions; 100 kg bar (NB), 80 kg bar with 20 kg band tension (B20), 75 kg bar with 25 kg band tension (B25) and 70 kg bar with 30 kg band tension (B30). Muscle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
(40 reference statements)
3
10
0
Order By: Relevance
“…Using the absolute load would scale down the load in the elastic band-conditions hence causing lower force output but greater velocity when compared to using the same relative load. This could also explain the decreased muscle activation in the elastic band-conditions as observed in the previous studies (Galpin et al, 2015;Heelas et al, 2019). Our force-data are supported by Swinton et al (2011) who compared deadlift using free weights and free weights + chains.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Using the absolute load would scale down the load in the elastic band-conditions hence causing lower force output but greater velocity when compared to using the same relative load. This could also explain the decreased muscle activation in the elastic band-conditions as observed in the previous studies (Galpin et al, 2015;Heelas et al, 2019). Our force-data are supported by Swinton et al (2011) who compared deadlift using free weights and free weights + chains.…”
Section: Discussionsupporting
confidence: 88%
“…However, the free weight condition appeared favorable for both average and peak force. Heelas et al (2019) found similar mean activation between the free weight-and band conditions, although free weights led to a higher peak activation in the semitendinosus and medial gastrocnemius. Importantly, both studies matched the load in the upper position i.e., the band and free weight-conditions developed the same absolute load in the top position.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations